THE ROLE OF GENDER-BASED ANALYSIS IN ENHANCING SOCIETAL SECURITY. A CASE STUDY OF ROMANIA’S APPROACH TO COVID-19 PANDEMIC AND ITS IMPACT ON A SELECT NUMBER OF GENDER CATEGORIES - Aura CODREANU; Cristina ANTONOAIE (Journal of Defense Resources Management, 2023)
Societal security has become nowadays an important pair of lenses for discussing identity in a multilayered fashion within the context of an enlarged security concept. The complexity deriving from that engenders the necessity to identify and use new tools for reliably defining communities and their specific identities in order to better understand how state-wise strategies and policies can raise security risks when disregarding those communities’ needs and interests. In this respect, the goal of this article is to demonstrate the benefits of employing a gender-based perspective in defining societal security. Hence, it focuses on the possible correlations that can be conceptually identified between societal security and gender perspective. Then, the article exemplifies how a gender-based analysis can contribute to better societal security approaches by discussing Romania’s strategic approach to the Covid-19 pandemic and the possible observations deriving from that.